SKILLS OVER DEGREES: RETHINKING TALENT ACQUISITION IN THE MODERN ERA - Muhammad Ali Siregar; Tibrani; Lukmanul Hakim (RADJA PUBLIKA, 2026)
The traditional model of talent acquisition, which privileges four-year degrees as a primary hiring proxy, is increasingly misaligned with the demands of the modern economy. This analysis argues for a fundamental paradigm shift toward skills-based hiring, where verified competencies take precedence over formal credentials. The article reviews the drivers of this change—including technological disruption, the skills gap, and the imperative for equity—and presents evidence that skills-based assessments lead to a larger, more diverse talent pool, superior job performance, and higher retention. Crucially, it identifies a significant